ECABLE (External Catheter Flexible) innovation of catheter external products for women - Willman, Lamro Taruna; Afifah, Tasya; Banurea, Menda Natalia; Ismianti, Ismianti (OPSI, 2023)
The increasing age of humans leads to reduced strength and muscle mass. Increasing age can also cause a decrease in the function of other organs, such as the urinary tract so that some elderly people have difficulty moving places to urinate and need to use diapers. The types of urinary catheters on the market are intermittent catheters, suprapubic catheters, and external catheters. The purpose of this study was to design a special external catheter for women with the name Ecable. Ecable is designed according to the needs of users both the elderly themselves and people who care for the elderly. The method used in this design is design thinking. ecable consists of five major components: a urine bag, an alarm, a hose, special underwear, and a urine funnel. The advantages offered by this product are easy to install and remove, comfortable to use, minimize unpleasant odors, there is a full urine bag detection alarm, minimize the cause of irritation, and are cost-effective because they can be used repeatedly.  This catheter is expected to help the elderly and caregivers to overcome existing needs.